Mortality in an off-shore predator critical habitat during the Northeast Pacific marine heatwave - Gálvez, Casandra; Raverty, Stephen; Galván-Magaña, Felipe; Field, Cara L.; Elorriaga-Verplancken, Fernando R. (Frontiers in Marine Science, 2023)
Defining baseline mortality and trends in wildlife populations is imperative to understand natural and anthropogenic threats to overall population health and improve conservation measures for species, particularly in geographically confined habitats. The Guadalupe fur seal Arctocephalus townsendi (GFS) is a threatened pinniped that ranges throughout the west coast of Mexico with sporadic dispersion to higher latitudes. Their breeding habitat is restricted to Guadalupe Island, Mexico, which is vulnerable to periodic and cyclic warming of the Northeast Pacific Ocean. The impacts of environmental change on GFS health and reproductive success at Guadalupe Island are poorly defined and the aim of this study was to establish baseline pup (GFSn) mortality rates and primary causes of death during the 2013-2016 breeding seasons at Guadalupe Island. Interannual mortality rates and causes of death were compared by year, breeding seasons and by geographic location. The highest mortality rate in GFSn was in 2015 (14.7%), followed by 2014 (8.2%), 2016 (6.7%) and 2013 (5.6%). The presumptive causes of mortality of GFSn were consistent with other published long term otariids health surveys and included: emaciation (49%), trauma (24%), infectious disease (8%), drowning (4%) stillbirth/perinatal mortality (4%) and undetermined (11%). However, in 2015 and coinciding with northeast Pacific marine heatwave in 2014-2016, emaciation accounted for 54% of GFSn mortality in contrast to 9% in 2013. For GFSn, terrestrial habitat may influence mortality rates and causes of mortality but like other marine predators, marine habitat features, such as an increase in sea surface temperature are associated with changes in maternal care, nutritional status and pups survival. Monitoring mortality rate and causes in GFSn at Guadalupe Island is crucial to establish baseline health trends, document potential impacts on species demographics and recruitment during marine heatwaves and potential consequences in population recovery.